Sexual violence in a relationship – the scale and characteristics of the phenomenon: Sexual violence in a relationship – the scale and characteristics of the phenomenon (Archives of Criminology, 2025)
The main aim of the study was to estimate the scale of sexual violence experienced by women in relationships. The study was nationwide and was part of a pan-European victimisation study on gender-based violence (GBV). The study was carried out in 2021–2023 by Statistics Poland and was co-financed by Eurostat. It used a survey questionnaire prepared by Eurostat, and involved a group of 5,247 respondents from all sixteen voivodeships of Poland. The article presents the results regarding sexual violence in a relationship; therefore, only the questionnaires completed by women who werecurrently or previously in a relationship were analysed. A total of 5,242 survey questionnaires that met the established criteria were collected.According to the results, nearly 4% of the women had experienced serious acts of sexual violence in a relationship by a current or former partner. Sexual violence from a partner is usually combined with psychological and physical violence. Such acts are extremely rarely reported – typically only when there are physical injuries which require medical attention.